The Effects of Tourist Activities on Bird Species Diversity in the Tambing Lake Area, Lore Lindu National Park, Central Sulawesi, Indonesia - Sustri; Sri Ningsih; Naharuddin; Rukmi; Alam Ansary (Jurnal Penelitian Pendidikan IPA, 2026)
The increase in tourism activity in the Lake Tambing area has the potential to put pressure on the ecosystem, especially on wildlife that is sensitive to human disturbance. Lake Tambing located in Lore Lindu National Park, Central Sulawesi, is an area of ​​high ecological value and home to a variety of endemic flora and fauna. This study aimed to analyze the potential of fauna, particularly bird populations, as indicators of ecological conditions and to observe the impact of tourism activities on bird diversity. The study was conducted from February to June 2025 at the camping ground and on the trackings trail using the line transect method. Data analysis included the Shannon-Wiener diversity index, evenness index, dominance index, and t-tests for comparisons between habitats. The study identified 56 bird species from 30 families, of which 26 are endemic to Sulawesi. Diversity index values ​​ranged from 2.79 to 3.28, indicating moderate to high levels of diversity. Statistical tests showed that tourist activity had no significant impact on bird diversity in either habitat type. This indicates that anthropogenic disturbance at Lake Tambing remains at a low level. These findings provide an important scientific basis for sustainable tourism practices, standardization of birdwatching site design, and effective endemic species conservation efforts in the Lake Tambing area.